First Two Brazilian Cases: Correction of Ascending Aortic Aneurysm and Aortic Valve Stenosis with Sutureless/Rapid Deployment Aortic Prosthesis - Silva,Isaac Azevedo (2019)
Abstract Ascending aortic aneurysm is usually associated with aortic valve diseases, especially aortic stenosis. The standard technique involves the substitution of the dilated aortic segment with a Dacron tube and replacement of the aortic valve with a regular prosthesis. The correction of ascending aortic aneurysm with aortic valve replacement using the new sutureless and rapid deployment prosthesis was performed by a minimally invasive approach and for the first time in a Brazilian Center.